КРЕМНИЙ С НАНОКЛАСТЕРАМИ АТОМОВ МАРГАНЦА – НОВЫЙ МАТЕРИАЛ ДЛЯ ТЕНЗОДАТЧИКОВ - Турсынбаев, С.А. (SCIENCE and SOCIETY, 2020)
The article presents the data that tensorial properties of silicon with nanoclasters of manganese atoms differ from that of ordinary semiconductors, including from that of silicon doped with different impurity atoms. It is found that increase of temperature and illumination substantially increase tensorial sensitivity of the material. The obtained results are explained by the widening of energetic spectrum in both nanoclasters (quantum dots) and formed minizones in the material.